Nanofiller Reinforcement versus Surface Treatment Effect on the Mechanical Properties of Syntactic Foams - Zhang, Liying (2017)
Syntactic foams are one of the special kinds of composite materials which can be prepared in a mechanical way by mixing hollow particles (the filler) with a resin system (the binder). To improve the mechanical properties of syntactic foams, in our work, carbon nanofibers (CNFs) were added to reinforce the syntactic foam. Results showed that although the presence of carbon nanofiber improved the mechanical properties of the syntactic foam, it dramatically increased the density, i.e., destroyed the main advantage of syntactic foams. In addition, the introduction of CNFs could cause difficulty in fabrication and increase the production cost. In order to overcome these problems, two approaches of the surface treatment of hollow microspheres, namely coupling agent and polydopamine (PDA) coating, were applied. Results showed that better interfacial adhesion between hollow microspheres and matrix could be induced from both coupling agent and PDA treated hollow microspheres, which led to the enhancement in mechanical properties of the syntactic foam while maintaining their low density. Compared with the coupling agent approach, the facile one-step PDA coating was much more effective. The failure mechanisms of the CNFs reinforced syntactic foam (CNFRSF) and the syntactic foam containing treated hollow microspheres were discussed in detail. © (2015) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.